2022
DOI: 10.21071/psye.v14i3.15071
|View full text |Cite
|
Sign up to set email alerts
|

Perfiles motivacionales de los estudiantes españoles PISA 2018: caracterización emocional y diferencias en rendimiento académico

Abstract: En las últimas décadas se han llevado a cabo diferentes estudios que profundizan en las condiciones que explican el compromiso de los individuos con las tareas académicas. Estas investigaciones evidencian la necesidad de combinar factores cognitivos —las capacidades, conocimientos o estrategias— con aspectos de carácter motivacional, como la disposición, la intención o las creencias autorreferidas. En este contexto se sitúa este estudio, que tiene por objeto identificar perfiles motivacionales, en función de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several studies have highlighted how important it is for PE teachers to design their classes to encourage task-oriented learning climates-this can be decisive, both for achieving positive results in PE classes and for increasing active lifestyles outside of school [20,46]. These results could be due to the fact that when students have a task-oriented disposition to achieve their goals, they believe the success of the final result depends on their own effort, interest, and self-learning [47][48][49], with these behaviours being related to a lower probability of them abandoning sports practice in their leisure time [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted how important it is for PE teachers to design their classes to encourage task-oriented learning climates-this can be decisive, both for achieving positive results in PE classes and for increasing active lifestyles outside of school [20,46]. These results could be due to the fact that when students have a task-oriented disposition to achieve their goals, they believe the success of the final result depends on their own effort, interest, and self-learning [47][48][49], with these behaviours being related to a lower probability of them abandoning sports practice in their leisure time [31].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the mediating role of satisfaction with PE, several studies have found that when a student has fun and feels satisfied with PE classes, their intention to be active in their leisure time will increase [10,20,28], with task orientation being a strong predictor of satisfaction with PE [12]. This relationship could be due to the fact that when adolescents are task-oriented, they tend to make an effort in their personal development, focusing their satisfaction on self-improvement [47,50,51], thus increasing their satisfaction with PE [12,48]. Various authors have highlighted the importance of strengthening student satisfaction and motivation in order to continue physical activity outside the school classroom [3,32,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%